Application of Problem-Based Learning Models and Puzzle Media to Improve The Learning Outcomes - Maya Indrasari; Subiyantoro, Singgih; Hastuti, Dwi (Cognitive Development Journal, 2023)
The impact of the Covid-19 pandemic on education in Indonesia has led to a phenomenon known as learning loss. In response, teachers are required to innovate by applying strategies and learning models that enhance both the learning process and student outcomes. This study aims to describe the use of the Problem-Based Learning (PBL) model and puzzle media in improving student learning outcomes in Pancasila and Civic Education for first-grade elementary students. This research is a type of Classroom Action Research (CAR). The subjects of the study were 17 first-grade students at SDN Genengsari 03. Data were collected using test instruments and observation techniques. The data analysis employed a comparative descriptive technique by comparing the percentage of students meeting the minimum score, as well as the maximum and average scores between the first and second cycles. The results indicated an improvement in learning outcomes. In the pre-cycle, 8 out of 17 students, or forty-seven percent, achieved the minimum competency score, with an average score of 61. In the first cycle, 11 out of 17 students, or sixty-four percent, reached the minimum score, with an average score of 81. In the second cycle, 16 out of 17 students, or ninety-four percent, met the minimum score, with an average score of 88. In conclusion, the use of the Problem-Based Learning model and puzzle media proves to be effective in improving the learning outcomes of first-grade elementary students. Overall, this research contributes to enhancing student achievement and the quality of learning.